Risk of major cardiovascular and cerebrovascular complications after elective surgery in patients with sleep-disordered breathing: A retrospective cohort analysis. Issue 8 (August 2020) - Chaudhry, Rabail; Suen, Colin; Mubashir, Talha; Wong, Jean; Ryan, Clodagh M.; Mokhlesi, Babak; Chung, Frances
Abstract : BACKGROUND: There is limited and conflicting data on whether sleep-disordered breathing (SDB) is associated with postoperative major cardiovascular and cerebrovascular events (MACCE), and mortality. OBJECTIVES: To determine whether SDB is associated with increased risks of MACCE, mortality and length of hospital stay. DESIGN: Retrospective cohort analysis from the Nationwide Inpatient Sample. SETTING: Adults who underwent elective abdominal, orthopaedic, prostatic, gynaecological, thoracic, transplant, vascular or cardiac surgery in the United States of America between 2011 and 2014. PATIENTS: The study cohort included 1813 974 surgical patients, of whom 185 615 (10.2%) had SDB. Emergency or urgent surgical procedures were excluded. MAIN OUTCOME MEASURES: The incidences of MACCE, respiratory and vascular complications, in-hospital mortality and mean length of hospital stay were stratified by SDB. Linear and logistic regression models were constructed to determine the independent association between SDB and outcomes of interest. RESULTS: The incidences of MACCE [25.3 vs. 19.8%, odds ratio (OR) 1.20, P < 0.001] and respiratory complications (11.75 vs. 8.0%, OR 1.43, P < 0.001) were significantly higher in patients with SDB than in those without SDB. SDB was associated with higher rates of atrial fibrillation (14.7 vs. 10.8%, P < 0.001), other arrhythmias (6.0 vs. 5.4%, P < 0.001) and congestive heart failure (9.8 vs. 7.1%, P < 0.001). SDB patients had a lower rate of myocardial infarction (3.1 vs. 3.4%, OR 0.69, P < 0.001), lower mortality (0.6 vs. 1.3%, P < 0.001) and shorter length of hospital stay (4.8 vs. 5.2 days, P < 0.001). CONCLUSION: SDB was associated with increased risks of MACCE, and respiratory and vascular complications, but had a lower incidence of in-hospital mortality and shorter length of hospital stay. Abstract : Supplemental Digital Content is available in the text